Electron spin resonance study on Mo-SiO₂ and Mo-TiO₂ with adsorbed benzene - Ignatovych, M.; Teslenko, V.; Eremenko, A.; Ogenko, V.; Chuiko, A. (Поверхность, 2002)
The study is devoted to ESR-investigation of the primary processes upon chemisorption of benzene molecules onto the molybdenum supported on dispersed SiO₂ and TiO₂ samples. It has been confirmed that benzene chemisorption onto the Mo⁶⁺ species results in one-electron transfer in the ground state and paramagnetic species formation, namely reduced molybdenum species (Mo⁵⁺ species) and radicals of benzene. Computer treatment of ESR experimental data revealed that there are several types of Mo⁵⁺ species and benzene radicals, the assignment of which is proposed.